2012
DOI: 10.1523/jneurosci.6387-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Regulation during Decision Making Shifts Behavioral Control between Ventromedial and Dorsolateral Prefrontal Value Systems

Abstract: Cognitive regulation is often used to influence behavioral outcomes. However, the computational and neurobiological mechanisms by which it affects behavior remain unknown. We studied this issue using an fMRI task in which human participants used cognitive regulation to up- and down-regulate their cravings for foods at the time of choice. We found that activity in both ventromedial prefrontal cortex (vmPFC) and dorsolateral prefrontal cortex (dlPFC) correlated with value. We also found evidence that two distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
212
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(234 citation statements)
references
References 44 publications
21
212
0
1
Order By: Relevance
“…A recent meta-analysis indicated that, across several studies using cognitive reappraisal, fear extinction, or placebo manipulations, regulating negative emotions showed converging activation within a subregion of the vmPFC (Diekhof et al, 2011). This investigation and other studies on the neural mechanisms of emotion regulation (Urry et al, 2006;Johnstone et al, 2007;Delgado et al, 2008b) have suggested that vmPFC activations observed during regulation are consistent with a role in cognitive control. Because this meta-analysis and most existing studies of reappraisal focused only on the regulation of negative affect, an alternative explanation remains: the increased signal in the vmPFC reflects the change in emotional value after emotion regulation.…”
Section: Introductionsupporting
confidence: 83%
“…A recent meta-analysis indicated that, across several studies using cognitive reappraisal, fear extinction, or placebo manipulations, regulating negative emotions showed converging activation within a subregion of the vmPFC (Diekhof et al, 2011). This investigation and other studies on the neural mechanisms of emotion regulation (Urry et al, 2006;Johnstone et al, 2007;Delgado et al, 2008b) have suggested that vmPFC activations observed during regulation are consistent with a role in cognitive control. Because this meta-analysis and most existing studies of reappraisal focused only on the regulation of negative affect, an alternative explanation remains: the increased signal in the vmPFC reflects the change in emotional value after emotion regulation.…”
Section: Introductionsupporting
confidence: 83%
“…Several functional neuroimaging studies have revealed that in particular the ventromedial prefrontal cortex (vmPFC) subserves the computation of an overall subjective value of choice options and thereby biases decisions (Kable and Glimcher, 2009). Dorsal and ventrolateral PFC (dlPFC and vlPFC, respectively) have been shown to modulate vmPFC activity and are involved in inhibitory control processes (Hare et al, 2009;Hutcherson et al, 2012) as well as emotional self-regulation (Ochsner and Gross, 2008). For example, activity of the vmPFC was found to be modulated by lateral PFC activity in individuals who are successful (self-) controllers of their dietary choices (Hare et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Luo et al (23) showed that striatal activity is greater when participants are presented with immediate rewards versus preference-matched delayed rewards. On the other hand, more patient behavior may result from control processes that bias attention away from immediate rewards and/or emphasize the importance of future goals (24,25). There are several studies that show that individual differences in future orientation are associated with more patient choices (1,21,26).…”
mentioning
confidence: 99%